The Effect of Job Rotation on Employee Performance with Motivation as a Mediating Variable - Ngatimun, Ngatimun (Publisher Cv. Inara, 2023)
The research aims to provide empirical evidence of the influence of job rotation and motivation on employee performance. Further empirical evidence with motivation as a mediating variable between job rotation and employee performance. The research data is primary data with a research sample of 80 respondents. Data analysis using path analysis and has met classical assumption testing. The research results indicate that job rotation has no effect on employee performance, while motivation has a significant effect on employee performance. Furthermore, it was found that motivation did not mediate the effect of job rotation on employee performance. Job rotation for employees is not a factor that can improve performance so it is unable to motivate KPP Pratama Sidoarjo Selatan employees.